USE OF WEB-BASED POETIC DEVICE TOOLS AS A LEARNING MEDIA FOR CREATIVE WRITING OF ENGLISH POETRY - Sarif Syamsu Rizal; Sri Oemiati; Haryati Sulistyorini (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
This research is entitled "Use of Web-Based Poetic Device Tools as a Learning Media for Creative Writing of English Poetry" The benefits of this research are both theoretical and practical. Theoretically, this study can be used to learn more about how to teach English poetry and creative writing using Web-Based Poetic Device Tools. Practically, to develop abilities in the use of Web-Based Poetic Device Tools as a medium for original English poem creation. The urgency of the research's findings will be able to expand the use of English poetry tool sites in general E-Learning implementation and can enhance the language industry, particularly innovative English poetry composing. The method of this research is Research and Development used to produce certain products, Models for Creative Writing of English Poetry Using Web-Based Poetic Device Tools and Simulation of the effectiveness of these products. The concept of scientific knowledge of poetry and poetry writing, the recognition and application of the use of web-based online poetic tools, the model, method, and steps of web-based poetic device tools in poetry writing, and English poetry writing simulation are the four findings that will be discussed in detail in the discussion.